Synthetic mRNA‐based differentiation method enables early detection of Parkinson's phenotypes in neurons derived from Gaucher disease‐induced pluripotent stem cells. (20th December 2020) - Akiyama, Tomohiko; Sato, Saeko; Ko, Shigeru B. H.; Sano, Osamu; Sato, Sho; Saito, Masayo; Nagai, Hiroaki; Ko, Minoru S. H.; Iwata, Hidehisa
Abstract: Gaucher disease, the most prevalent metabolic storage disorder, is caused by mutations in the glucocerebrosidase gene GBA1, which lead to the accumulation of glucosylceramide (GlcCer) in affected cells. Gaucher disease type 1 (GD1), although defined as a nonneuronopathic subtype, is accompanied by an increased risk of Parkinson's disease. To gain insights into the association of progressive accumulation of GlcCer and the Parkinson's disease phenotypes, we generated dopaminergic (DA) neurons from induced pluripotent stem cells (iPSCs) derived from a GD1 patient and a healthy donor control, and measured GlcCer accumulation by liquid chromatography‐mass spectrometry. We tested two DA neuron differentiation methods: a well‐established method that mimics a step‐wise developmental process from iPSCs to neural progenitor cells, and to DA neurons; and a synthetic mRNA‐based method that overexpresses a transcription factor in iPSCs. GD1‐specific accumulation of GlcCer was detected after 60 days of differentiation by the former method, whereas it was detected after only 10 days by the latter method. With this synthetic mRNA‐based rapid differentiation method, we found that the metabolic defect in GD1 patient cells can be rescued by the overexpression of wild‐type GBA1 or the treatment with an inhibitor for GlcCer synthesis. Furthermore, we detected the increased phosphorylation of α‐synuclein, a biomarker for Parkinson's disease, in DA neurons derived from a GD1 patient, which was significantly decreased by the overexpression of wild‐type GBA1. These results suggest that synthetic mRNA‐based method accelerates the analyses of the pathological mechanisms of Parkinson's disease in GD1 patients and possibly facilitates drug discovery processes. Abstract : Synthetic mRNA‐based expression of transcription factors enhanced induced pluripotent stem cell differentiation and enabled early (10 days) detection of a risk factor of Parkinson's disease, i.e. the accumulation of glucosylceramide (GlcCer) in Gaucher patient neurons. This rapid differentiation method also enabled to detect the phosphorylation of α‐synuclein—a critical Parkinson's disease‐linked phenotype.